Assessment of selected Saudi and Yemeni plants for mosquitocidal activities against the yellow fever mosquito Aedes aegypti - Shaza Al-Massarani; Amina El-Shaibany; Nurhayat Tabanca; Abbas Ali; Alden S. Estep; James J. Becnel; Fatih Goger; Betul Demirci; Ali El-Gamal; K. Husnu Can Baser (Elsevier, 2019)
As part of our continuing investigation for interesting biological activities of native medicinal plants, thirty-nine plants, obtained from diverse areas in Saudi Arabia and Yemen, were screened for insecticidal activity against yellow fever mosquito Aedes aegypti (L.). Out of the 57 organic extracts, Saussurea lappa, Ocimum tenuiflorum, Taraxacum officinale, Nigella sativa, and Hyssopus officinalis exhibited over 80% mortality against adult female Ae. aegypti at 5 μg/mosquito. In the larvicidal bioassay, the petroleum ether extract of Aloe perryi flowers showed 100% mortality at 31.25 ppm against 1st instar Ae. aegypti larvae. The ethanol extract of Saussurea lappa roots was the second most active displaying 100% mortality at 125 and 62.5 ppm. Polar active extracts were processed using LC-MS/MS to identify bioactive compounds. The apolar A. perryi flower extract was analyzed by headspace SPME-GC/MS analysis. Careful examination of the mass spectra and detailed interpretation of the fragmentation pattern allowed the identification of various biologically active secondary metabolites. Some compounds such as caffeic and quinic acid and their glycosides were detected in most of the analyzed fractions. Additionally, luteolin, luteolin glucoside, luteolin glucuronide and diglucuronide were also identified as bioactive compounds in several HPLC fractions. The volatile ketone, 6-methyl-5-hepten-2-one was identified from A. perryi petroleum ether fraction as a major compound. Keywords: Medicinal plants, Mosquito control, Aedes aegypti, Phenolic acids, Flavonoids, LC-MS/MS, Headspace-SPME, Aloe perryi volatile constituents, 6-Methyl-5-hepten-2-one